Take the bull by the horns - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Livestock keeping in urban areas. A review of traditional technologies based on literature and field experiences FAO Animal and Health Papers, No 151, 2001. 72 pp. ISBN 9251045755 US$14 Euro 14.20